Pregnancy After Hysteroscopic Endometrial Ablation Without Endometrial Preparation: A Report of Five Cases and a Literature Review - Chang-Sheng Yin (Elsevier, 2010)
Objective: Treating menorrhagia in women of reproductive age by endometrial ablation (EA) decreases menstrual flow and increases quality of life. However, unexpected pregnancy and associated complications are challenges following EA. Materials and Methods: From January 2000 to March 2008, a total of 356 women aged 26-45 years with persistent menorrhagia underwent total hysteroresectoscopic EA with follow-up at our hospital and were retrospectively evaluated. We also performed a literature search for articles reporting pregnancy after EA published between January 1983 and June 2008. Results: Overall, 123 pregnancies after EA have been reported in the English literature, including five pregnancies among 356 women who underwent EA at our hospital. Fifty-nine (48%) of 123 pregnancies were terminated at the mother's request. The remaining 64 pregnancies were associated with spontaneous abortion (28%, 17/64), premature rupture of membranes (16%, 10/64), prematurity (31%, 19/64), cesarean section (44%, 27/64), and placental adherence complications (25%, 17/64) which necessitating hysterectomy in 10 women. Four tubal ectopic, two cornual and two cervical ectopic pregnancies were reported. The ectopic pregnancy rate was 6.5% (8/123). There were nine perinatal deaths, corresponding to a perinatal mortality rate of 14% (9/64). Five babies had congenital anomalies, including craniosynostosis (1 case), a set of twins with Down syndrome (1 case), agenesis of the corpus callosum (1 case), bilateral talipes (1 case), and one case of fetal malformation caused by intrauterine synechiae. The only maternal death was a 29-year-old woman with spontaneous rupture of her unscarred uterus and massive intraabdominal hemorrhage at 24 weeks of gestation. Conclusion: Clinicians must recognize the potential complications associated with pregnancy after EA. Appropriate postoperative contraception and follow-up of menstrual patterns are strongly recommended.